Stability for seed yield and component traits in Indian mustard (Brassica juncea L.) under Jharkhand condition (Journal of Oilseed Brassica, 2026)
Fifty three genotypes of Indian mustard [Brassica juncea (L.) Czern & Coss.] consisting of 13 parents and 40 crosses were sown during Rabi 2014-15 under three different dates of sowing i.e. 21st October, 06th November and 21st November, with objective to test genotype-environmental (G X E) interaction and phenotypic stability for seed yield and its component traits. The experiment was laid out in randomized complete block design replicated two times. Timely sown (21st October) genotypes showed higher mean for seed yield/plant while late sown (21st November) genotypes showed lower mean due to forced maturity. Sufficient G X E interaction was exhibited by the genotypes for all the characters. All 53 genotypes were tested for 3 stability parameters, viz. mean, bi and S2 di. The environment (linear) was highly significant for all the characters, while the linear component of G X E interaction was highly significant for days to maturity only. Pooled deviation differed significantly for plant height, number of siliquae on main shoot, number of seeds/siliqua, total number of siliqua/plant, 1000-seed weight, days to maturity and seed yield/plant, suggesting the genotypes had varying level of stability over the sowing times for these characters. The parents viz. NRCDR-02, Pusa Bold and BPR 543-2 as well as the crosses viz. Pusa Bold x Pusa Mustard-21, Pusa Bold x RGN-73, Pusa Bold x JN032, Shivani x Heera and Shivani x BPR 543-2 exhibited high mean and showed stable performance for seed yield/plant. Stability parameters indicated that BAUSM-92-1-1 (1000-seed weight and days to maturity), Pusa Bold (seed yield/plant and days to maturity) and BAUM-2007 x JN-032 (total number of siliqua/plant and number of seeds/siliqua) were fairly stable across the environments. These genotypes can be utilized to develop stable strains having wider adaptability for different sowing times.